2014
DOI: 10.1002/iid3.23
|View full text |Cite
|
Sign up to set email alerts
|

A novel and well tolerated mite allergoid subcutaneous immunotherapy: evidence of clinical and immunologic efficacy

Abstract: Allergy to house dust mite is one of the most common causes of allergic rhinitis. A novel tyrosine-adsorbed, modified allergen product, Acarovac Plus, developed for the treatment of perennial mite allergy seeks to address the underlying cause of allergic rhinitis in this instance. One of two dosing regimens may be used, either the Conventional Regimen or the Cluster Regimen. We sought to compare the efficacy and safety of a specific immunotherapy, developed for the treatment of perennial mite allergy, administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 23 publications
4
30
0
1
Order By: Relevance
“…The clinical efficacy of another DPT subcutaneous immunotherapy product (DPT allergoid adsorbed to L -tyrosine) was demonstrated using a similar nasal provocation test in patients with allergic rhinitis and/ or asthma secondary to DPT hypersensitivity [25]. The study evaluated two different dosing schedules of DPT extract: a conventional escalating dose regimen over 3 weeks and a cluster schedule (more than 1 dose/visit) over 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy of another DPT subcutaneous immunotherapy product (DPT allergoid adsorbed to L -tyrosine) was demonstrated using a similar nasal provocation test in patients with allergic rhinitis and/ or asthma secondary to DPT hypersensitivity [25]. The study evaluated two different dosing schedules of DPT extract: a conventional escalating dose regimen over 3 weeks and a cluster schedule (more than 1 dose/visit) over 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Others also observed similar phenomenon. Such as Roger et al treated a group of patients with allergic rhinitis and found that the SIT had no significant effect on concentrations of total IgE, specific IgE or Th2 cytokines, although satisfactory relief of allergic rhinitis symptoms was declared by most patients in the period of the treatment 10 . Glover et al found that no effect of SIT on asthma 11 .…”
Section: Discussionmentioning
confidence: 99%
“…European IT practices have traditionally used aluminum adjuvants and more recently other depot adjuvants such as tyrosine for allergoid SCIT . The use of these depot adjuvants results in a slower release of the allergoid and has been associated with fewer SRs . The increased safety associated with this slower release, in principle parallels the use of a slower buildup phase.…”
Section: Discussionmentioning
confidence: 99%